DISTRIBUTION AND GEOBOTANICAL STUDIES OF THE MEDICINAL PLANT CAPPARIS HERBACEA WILLD. IN THE SOUTHERN REGIONS OF KAZAKHSTAN (Experimental biology, 2023)
Conservation of biodiversity has now become one of the most important issues in the world. Among them, the conservation of medicinal plants requires special protection. Today, medicinal plants are widely used in scientific medicine. Its main purpose is to prepare medicinal preparations on the basis of medicinal plants. Huge territories of Kazakhstan are provided with rich natural diversity. Our country has unique plants, adapted to life in the desert. In addition, the flora is rich in forest and steppe species. In recent years, the country's environmental problems have become more complex. The issue of conservation of medicinal plants is a pressing environmental concern. The pharmaceutical industry in Kazakhstan is still in need of development. Therefore, the development of the pharmaceutical industry has become an urgent issue in the country. Intensive integrated use (highland pastures, hayfields, developed cattle breeding, as well as use as a recreation area) of mountain and foothill territories, has caused significant anthropogenic changes in flora and vegetation in recent years. The relevance of the study, is the study of the medicinal plant Capparis heerbacea Willd. which grows mainly in the deserts, semi-deserts and steppes of Central Asia and Kazakhstan. This species is well adapted to different abiotic conditions and was therefore selected for the present study. The research work was carried out in 2020-2022. Classical botanical methods were used in the work. These include: route surveys, ecological systematics, ecological geography, methods of studying cenopopopulations. As a result of research work communities are characterized by the following data: Populations which are in Turkestan region and grow in disturbed areas, gradually increase the number of their individuals and thereby restore the local flora or form the conditions for the formation of new communities and populations of other species. And in the Kyrgyz Alatau population, the ecological condition is stable, which is shown by the mosaic distribution of the study species. The study showed that C. herbacea can be one of the main dominant species for a particular area or locality and an edificator for some ephemeral or ephemeroid species.